The Usage Of 'turnitin' As An Innovative Educational Tool: Inculcating Critical Thinking In Integrating Naqli And Aqli For Subject Of Malaysian Economy - Fuadah Johari; Mohammad Haji Alias; Asma Abdul Rahman; Mohd Firdaus Ibrahim (Elsevier BV., 2024)
Procedia - Social and Behavioral Sciences 195 ( 2015 ) 821 – 827